filmov
tv
Prove that sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/1-2cos^2a
![preview_player](https://i.ytimg.com/vi/4pwS9DQOssI/sddefault.jpg)
Показать описание
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/1-2cos^2a
(sinA+cosA) % (sinA-cosA) + (sinA-cosA) % (sinA+cosA) = 2 % (1-2cos2A)
prove sina +cosa/sina-cosa +sina-cosa/sina+cosa=2/1-2cos2a
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/sin2a-cos2a=2/2sin2a-1=2/1-2cos2a
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2 sec^2a/tan^2a-1
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/sin2a-1
cota+coseca-1/cota-coseca+1=1+cosa/sina
prove that sina/cota+coseca=2+sina/cota-coseca
sina+cosa/sina-cosa+sina-cosa/sina+cosa=1/sin2a-cos2a
cosa+sina/cosa-sina-cosa-sina/cosa+sina=2tan2a
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2sin2a-cos2a
(sinA+cosA) % (sinA-cosA) + (sinA-cosA) % (sinA+cosA) = 2 % (1-2cos2A)
prove sina +cosa/sina-cosa +sina-cosa/sina+cosa=2/1-2cos2a
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/sin2a-cos2a=2/2sin2a-1=2/1-2cos2a
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2 sec^2a/tan^2a-1
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/sin2a-1
cota+coseca-1/cota-coseca+1=1+cosa/sina
prove that sina/cota+coseca=2+sina/cota-coseca
sina+cosa/sina-cosa+sina-cosa/sina+cosa=1/sin2a-cos2a
cosa+sina/cosa-sina-cosa-sina/cosa+sina=2tan2a
sina+cosa/sina-cosa+sina-cosa/sina+cosa=2sin2a-cos2a
Prove that sina+cosa/sina-cosa+sina-cosa/sina+cosa=2/1-2cos^2a
(sinA + cosA)/(sinA-cosA)+(sinA - cosA)/(sinA+cosA)=2/(sin^2A-cos^2A)= 2/(2sin^2A-1)=2/(1-2cos^2A)
((sinA+cosA /sinA-cosA) +(SinA-cosA /sinA+cosA))=2/1-2cos square A #class10th #Short @ #youtube
Sina +cosa/sina-cosa+sina-cosa/sina+cosa=2/1-2cos2a || NCERT MATH SOLUTION by Majid sir
`(cosA+sinA)/(cosA-sinA) - (cosA-sinA)/(cosA+sinA) = 2tan2A`
#Trigonometry all formulas
If cosA+sinA =√2cosA then Prove cosA-sinA = √2sinA
prove that (1+sina+cosa)^2=2(1+sina)(1+cosa)
How to prove this|TRIGONOMETRY|PROBLEM|1+sinA=(sinA/2+cosA/2)^2|sub multiple angles|Question-1
Prove that (1+CotA+TanA)(SinA-CosA)/(Sec³A-Cosec³A) = Sin²ACos²A | Class 10 Math Trigonometry |
Prove that: ((SinA)^3 + (CosA)^3) / (SinA + CosA) = 1 - (1/2) Sin2A
TRIGONOMETRY | Prove (sinA +secA)^2 + (cosA + cosecA)^2 = (1 + secAcosecA)^2 || Q 9
(1+cosA+sinA)/(1-cosA+sinA)=cotA/2 | Trigonometry
(1+sina)^2 + (1-sinA)^2/cos^2A= 2(1+sin^2A/1-sin^2A) ||trigonometry|| Mathematics classes|| @PW
If SinA + 2CosA = 1 then prove that 2SinA - CosA = 2 | Class 10 | Trigonometry |
(1-sinA-cosA)²=2(1-sinA)(1-cosA) |Trigonometry
Prove that trigonometry sin^2 A= (1-cos2A)/2 & cos^2 A= (1+cos2A)/2 PART-8
Prove [(1 + SinA - Cos A) / (1 + Sin A + Cos A)]^2 = (1- CosA)/(1+ CosA)
Prove that sin²A/2 + sin²B/2 - sin²C/2 = 1 - 2cosA/2 + cosB/2 + sinC/2 | EDUTAINMENT ONLINE
Trigonometry. Prove that (1+sina-cosa/1+sina+cosa)^2=1-cosa/1+cosa. Trigonometry important questions
Show that Cos 3A + Sin 3A / Cos A — Sin A = 1 + 2 Sin 2A @EAG
Prove that (1+cota+tana)(sina-cosa)=seca/cosec^2a-coseca/sec^2a=sina.tana-cota.cosa | Trigonometry |
Prove (sin A + cosec A)^2 + (cos A + sec A)^2=7+ tan^2A + cot^2A | Q5 (viii)
to prove: (cosecA -secA)^2 = (1-cosA)/(1+cosA) #trignometry #mathsfreak
Комментарии